Quick cost estimation model for early order stage - Mohamed Rasin, Mohamad Zaihirain; Ismail, Napsiah; Salit, Mohd Sapuan; Wong, Shaw Voon (Universiti Teknikal Malaysia Melaka, 2009)
On time quotation and accurate cost estimate are two important factors influencing the ability of a company to sustain its business operation. Failure to fulfill requests for quotation can severely effect its business survival. Late and uncompetitive quotations will result in lost of customers. It is vital for manufacturing companies to generate cost estimates quickly and accurately otherwise they might either loose their business or not make sufficient profit. Cost estimation process requires good knowledge in the structure of the part and its manufacturing processes. Cost estimation can be done with a high degree of accuracy but it takes too long and if it is done in a short period of time the accuracy is usually quite poor. Generating detailed process plan requires a substantial amount of time and data. Unfortunately, not all necessary information is available during the costing stage. This paper shows the possibility of developing part cost estimate without having to construct its detail process plan. It presents a model for estimating part process cost which allows a cost estimate to be generated quickly with certain degree of accuracy by utilizing parametric techniques and part feature representation.